Understanding the complexities of financial support for students in grant-funded STEMM training programs - Romero, Ana L.; Cobian, Krystle P.; Martín, Patricia A. (Frontiers in Education, 2025)
IntroductionThere are lessons to be learned from campuses providing financial support to students involved in grant-funded science, technology, engineering, mathematics, and medicine (STEMM) training initiatives. We examine students’ perspectives on financial support from the Building Infrastructure Leading to Diversity (BUILD) program, funded by the National Institutes of Health.MethodsWe analyzed qualitative data collected from 122 BUILD undergraduate participants during site visits to the 10 NIH-sponsored BUILD programs using generic qualitative inquiry.ResultsUsing Social Cognitive Career Theory (SCCT) to guide qualitative data analysis, we found that students perceived BUILD funding to reduce financial stress and increase access to career training; however, the impact of aid was hampered by limitations in funding and financial aid processes.DiscussionFindings from this study reveal that financial support from BUILD often facilitated college entry and participation in biomedical research training experiences for students. While students viewed financial support as beneficial to their academic and professional trajectory, they also noted challenges with financial aid processes on campus. This study has implications for federal funding agencies, foundations, and higher education institutions, specifically in developing innovative disbursement processes to improve support and to reduce unintended harmful consequences for student recipients.